Relationship between exercise heart rate and music tempo preference - Larageorghis, C. I.; Jones, L.; Low, D. C. (Research Quarterly for Exercise and Sport, 2006)
The present study examined the predicted positive and linear relationship (Iwanaga, 1995a, 1995b) between exercise heart rate and music tempo preference. Initially, 128 undergraduate students (M age = 20.0 fears, SD = 0.9) were surveyed to establish their three favorite music artists. A separate experimental group of 29 undergraduates (M age - 20.3 years, SD = 1.2} selected the music of a single artist from the three highest-rated artists from the earlier survey. They reported their preference for slow, medium, and fast tempo selections from each artist for three treadmill walking conditions at 40%, 60%, and 75 % maximal heart rate reserve. A mixed-model 3x3x2 (Exercise Intensity x Music Tempo x Gender) analysis of variance was used to analyze the data. Results indicated there was no three-way interaction for music preference. There was, however, a significant (p < .05) two-way interaction for Exercise Intensity x Music Tempo (partial n² = .09) and a significant (p < .05) main effect for music tempo, with large differences evident between preference for medium versus slow tempo and fast versus slow tempo music at all exercise intern/lies (partial n² = . 78). Participants reported a preference for both medium and fast tempo music at low and moderate exercise intensities and for fast tempo music at high intensity. Only partial support was found for the expected linear relationship between exercise intensity and music tempo preference.